Estratégias para descompactação do solo por escarificação e hastes sulcadoras em sistema plantio direto - Drescher, Marta Sandra (2015)
In areas managed under no-till in southern Brazil the soil compaction process has been associated with structural degradation of subsurface soil layer, visible by changes in soil physical properties, morphological changes of roots and casual perception of crop yield reduction. As an alternative to mitigate this process or to prevent the soil reaches critical levels of compaction, farmers use mechanical chiseling to promote the disruption of the compacted layer and improve soil structure. However, the benefits of this practice on soil physical and hydraulic properties have shows short duration making necessary to search for alternative methods to mitigate soil compaction. In this sense, this paper aims to study the duration of the benefits of mechanical chiseling on physic-hydraulic soil properties, aiding in the understanding of soil reconsolidation time and the development of strategies to mitigate compaction based on the types of fertilizer furrow in the no-till seeders. Therefore, a study was conducted in Coxilha, in northern region of the Rio Grande do Sul state on an Oxisol, to assess the residual effect of chiseling. The treatments were composed by the control treatment (27 years under continuous no-till) and seven adoption times (0, 6, 12, 18, 24, 30 and 36 months) of no-till after mechanical chiseling. To assess the potential to mitigate soil compaction of the seeder furrow were evaluated three strategies: shanks plus disc to 0.10 m; shanks plus disc to 0.15 and double disc to 0.07 m depth. The treatments were compared by the soil physical and hydraulic properties of bulk density, relative density, pore distribution, penetration resistance, infiltration rate, water retention capacity, water store for plants, saturated hydraulic conductivity, unsaturated hydraulic conductivity and air permeability. The results indicated that the residuality of mechanical chiseling varies according to the evaluated physical-hydraulic attribute lasting only for one harvest to the bulk density, total porosity and macroporosity, 18 months for penetration resistance and 24 months for hydraulic conductivity and infiltration rate. There was no residual effect of chiseling for time periods longer than two years after tillage. The use of furrow shank type to 0.15 m deep, promoted the disruption of compacted layer with very similar benefits to those obtained with soil chiseling, indicating potential to use to mitigate soil compaction under no-till systems.